Regulation of egg formation in the oviduct of laying hen. Issue 3 (1st September 2018) - Sah, N.; Mishra, B.
Abstract : In the adult hen, the oviduct receives the ovum from the ovary and provides the biological environment for the formation and potential fertilisation of the egg. During egg formation, albumin, from the magnum is deposited around the yolk, followed by the eggshell membranes from the isthmus, which subsequently surround the egg. As the yolk traverses through the oviduct, calcium is deposited on to it, from the uterus, forming a hardened eggshell. Ovalbumin, avidin and ovomucin secreted from magnum provides content and antimicrobial activity in the egg-white. Collagen X and fibrilin 1 from the isthmus make up the fibrous eggshell membranes. Calbindin 1, ovocleidin-116 and secreted phosphoprotein 1 secreted from the shell gland contribute in calcium ion remodelling for eggshell mineralisation. This review summarises the expression pattern and functional role of genes having a leading role in the egg formation.